複雑な社会を有するハンドウイルカ属における長いコドモ期の適応的意義の解明 - 酒井, 麻衣; 40512299; Sakai, Mai
本研究では、野生・飼育ハクジラを対象にコドモ期の相互作用の記載を行った。野生ミナミハンドウイルカでは、初産の子は経産の子よりも生存率が低かった。また、母子間の遊泳距離には個体差があることや、母・息子間で社会的性行動をすることが示された。ハンドウイルカ母子の胸ビレで相手をこするラビングは、体表面の古い皮膚を落とす世話行動であることが明らかになった。イロワケイルカでは母による子の遊泳サポートは生後1か月間に頻繁に起き、それ以降は減少することがわかった。シャチ母娘間のラビングは、娘の成長に伴い送受の偏りが小さくなり、母も娘から利益を受ける関係に移行しつつあることが推察された。 In this study, interactions during juvenile periods were described in wild and captive bottlenose dolphins. In wild Indo-Pacific bottlenose dolphins, calves born from primiparous females had a lower survival rate than those born from parous female. Individual differences in swimming distance between mothers and calves and sociosexual behavior between mothers and sons were also demonstrated. Flipper rubbing in which mothers rub calves with its pectoral fins in bottlenose dolphins was found to be a caring behavior to remove old skin from the body surface. In Commerson's dolphins, mothers supported their offspring swimming frequently during the first month of life and decreased thereafter. In orca mother-daughter flipper rubbing, the send-receive bias decreased as the daughters grew older, suggesting that the mother was shifting to a relationship in which she also received some benefit from her daughter. 研究分野：動物行動学